Komplementarna interdyscyplinarność, interdyscyplinarna komplementarność - Kalaga, Tomasz (Er(r)go. Teoria - Literatura - Kultura, 2017)
Book review: Makoto Katsumori Niels Bohr’s Complementarity. Its Structure, History, and Intersections with Hermeneutics and Deconstruction, Boston Studies in the Philosophy of Science, Springer, 2011, 178 s. Publikacja anglojęzyczna